Variations in Newspaper Coverage on Water in the U.S. Intermountain West. (29th July 2019) - Flint, Courtney G.; Wynn, Elizabeth; Paveglio, Travis; Boyd, Amanda; Bullock, Cathy
Abstract: Water is a salient issue in the Intermountain West of the United States (U.S.), with concerns ranging from water scarcity and drought to intermittent flooding and water quality risks. This paper investigates coverage of water issues across seven newspapers in the core of the U.S. Intermountain West region. Newspapers have the potential to set agendas and influence perceived salience of issues among consumers. The Intermountain West region shares common concerns about water supply and demand, climate change, and water quality. We investigate whether or not local daily newspaper coverage of water issues provides a more local or regional sensitivity. Findings from this exploratory study reveal differences in water coverage across local daily newspapers. The overall volume of water‐related articles differed across newspapers as did proportion of articles on specific water topics and connecting issues. Coverage of local issues was more dominant than might be expected given mass media trends, but water geography in articles extended across the U.S. and the world in every newspaper studied. Variations in newspaper coverage of water issues suggests more local nuance persists despite the experience of common water issues across the region. Abstract : Research Impact Statement : Coverage of water varies across seven newspapers in the Intermountain West, thus potentially influencing local and regional agenda setting on water issues.